InGaAs Quantum Well Grown on High-Index Surfaces for Superluminescent Diode Applications - Wu Jiang; Fan Dongsheng; Li Shibing; Yu Shui-Qing; Li Zhenhua; Wang Zhiming; Guo Aqiang; Manasreh Omar; Salamo Gregory (Nanoscale Research Letters, 2010)
Abstract The morphological and optical properties of In0.2Ga0.8As/GaAs quantum wells grown on various substrates are investigated for possible application to superluminescent diodes. The In0.2Ga0.8As/GaAs quantum wells are grown by molecular beam epitaxy on GaAs (100), (210), (311), and (731) substrates. A broad photoluminescence emission peak (~950 nm) with a full width at half maximum (FWHM) of 48 nm is obtained from the sample grown on (210) substrate at room temperature, which is over four times wider than the quantum well simultaneously grown on (100) substrate. On the other hand, a very narrow photoluminescence spectrum is observed from the sample grown on (311) with FWHM = 7.8 nm. The results presented in this article demonstrate the potential of high-index GaAs substrates for superluminescent diode applications.